Dextrocardia with Situs Inversus and Ventricular Septal Defect in a 1-year-old female: A Case Report - Chandni P Daryanani; Vella Sianecha Azzah Tesla Bose; Tjong Michella Florencia; Haldvin Felix Theios; Agnes Yelin Kristianingsih (Medical Clinical Update, 2023)
Dextrocardia is a rare congenital anomaly characterized by the malposition of the heart in theright side of the thorax. The disorder is often accompanied by other developmental anomalies,and diagnosis is usually incidental. Some cases involve situs inversus totalis or reversal of the position of other organs. Ventricular septal defect (VSD) is the most common congenital heart defectobserved in children and is second only to bicuspid aortic valve as the most common congenitalabnormality in adults. Dextrocardia is a rare condition, with studies indicating incidence rates ofapproximately 1 in 12,000 pregnancies. Kartagener syndrome has a lower incidence rate of around1 in 30,000 live births, and situs inversus totalis was observed in roughly 50% of patients withprimary ciliary dyskinesia.